Tea and coffee consumption and the 15-Year risk of cardiovascular events: the Isfahan cohort study (ICS) - Raza Amani-Beni; Masoumeh Sadeghi; Fatemeh Nouri; Bahar Darouei; Noushin Mohammadifard; Maryam Boshtam; Ramesh Hosseinkhani; Nizal Sarrafzadegan (Nutrition Journal)
Abstract Background This study aimed to investigate the association between tea and coffee consumption and the 15-year incidence of cardiovascular events and mortality among the Iranian population. Methods The present study Data were obtained from the Isfahan Cohort Study (ICS), a prospective cohort study of ≥ 35-year-old healthy adults in central Iran from 2001 to 2017. This study was conducted using baseline data on tea and/or coffee consumption per day/week from ICS to identify the occurrence of any new cardiovascular events, including acute myocardial infarction (AMI), unstable angina (UA), stroke, cardiovascular disease (CVD), sudden cardiac death (SCD), cardiovascular mortality, and all-cause mortality. Results 5248 participants with complete data were included in the study. After full adjustments, compared to participants with the lowest tea intake, the risk of AMI was significantly higher for participants with the highest tea intake (hazard ratio (HR) = 1.83; 95% confidence interval (CI): 1.10, 3.07; p for trend = 0.060). Also, moderate-tea drinking was associated with a 66% increased risk of AMI compared to the lowest-tea drinking (HR = 1.66; 95%CI: 1.03, 2.70). No significant association was observed between tea consumption and other CVD events or all-cause mortality. Moreover, after full adjustment, no significant association was observed between tea intake above the median and cardiovascular events or all-cause mortality or between coffee consumption and study outcomes. Conclusions High tea consumption significantly increases the risk of AMI; however, high tea and coffee consumption had no significant association with other cardiovascular events. Future research is needed, especially in Iran and the Middle East, to clarify and evaluate more factors related to the complex nature of tea and coffee consumption and cardiovascular events.